2019
DOI: 10.1158/1535-7163.targ-19-b057
|View full text |Cite
|
Sign up to set email alerts
|

Abstract B057: BMS-986148, an anti-mesothelin antibody-drug conjugate (ADC), alone or in combination with nivolumab demonstrates clinical activity in patients with select advanced solid tumors

Abstract: Background: Mesothelin, a GPI-anchored cell surface protein, is highly expressed in several tumor types and can be targeted for antibody (ab)-based cancer therapy. BMS-986148 is a fully human IgG1 anti-mesothelin monoclonal ab conjugated to tubulysin to promote selective cytotoxic delivery to tumor cells. In preclinical models, combination of anti–mesothelin-tubulysin with anti–PD-1 promoted a synergistic antitumor response and influx of tumor-infiltrating lymphocytes. Here, we present initial data for BMS-986… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Others anti-mesothelin ADCs, like DMOT4039A, RC88 and BMS-986148, are under clinical evaluation (Table 2 ). The latter showed promising results when combined with nivolumab in patients with mesothelin-selected mesothelioma [ 87 ].…”
Section: Promising New Targets Under Investigationmentioning
confidence: 99%
“…Others anti-mesothelin ADCs, like DMOT4039A, RC88 and BMS-986148, are under clinical evaluation (Table 2 ). The latter showed promising results when combined with nivolumab in patients with mesothelin-selected mesothelioma [ 87 ].…”
Section: Promising New Targets Under Investigationmentioning
confidence: 99%
“…One group of drug candidates includes immunotoxins against mesothelin, a surface antigen particularly expressed on MM cells but also on normal mesothelium and other cell types. At various stages of clinical development, these drugs include anetumab ravtansine (Bayer Healthcare, BAY94-9343) [ 6 ], BMS-986148 (Bristol-Myers Squibb, New York, NY, USA) [ 7 ] and aMSLN-MMAE (Roche/Genentech, DMOT4039A, San Francisco, CA, USA) [ 8 , 9 ] ADCs. In addition, ADCs targeting CD228, PDL-1 and EGFR have been studied for MM treatment, carrying different payloads [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In principle, various cytotoxic payloads can be attached to the monoclonal antibodies (mAbs) that recognize tumor-associated proteins to achieve specific elimination. Although this strategy has indeed been studied for certain potential target proteins in MM [ 6 , 7 , 8 , 9 , 10 , 11 ], none of these studies has led to clinically approved ADC so far [ 3 , 12 ]. Therefore, it is essential to identify targetable proteins with defined expression patterns correlated with mesothelioma but with restricted expression in normal tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary data from a phase I/II trial (NCT02341625) with BMS-986148 monotherapy or in combination with nivolumab (anti-PD-1 inhibitor) against MSLN-expressing solid tumors showed that this anti-MSLN ADC was well tolerated (manageable adverse effects). Moreover, some efficacy was reported in MPM patients: 4% overall response rate (ORR) for monotherapy; 31% ORR when given in combination [110]. Durable responses (up to 9 months) were also observed.…”
Section: Antibody-drug Conjugatesmentioning
confidence: 99%